Digital Financial Literacy and its Impact on the Financial Well-Being of Small and Medium-Sized Industries - Permadi, Indra; Safitri, Niken; Fhatusyaadah, Eva (KnE Social Sciences, 2022)
According to various studies, the sustainability and performance of small and mediumsized enterprises (SMEs) are directly related to Indonesia’s financial well-being. Well-being, finance, and financial literacy are important indicators of SMEs’ welfare. The study aimed to understand the level of knowledge of SME owners with regard to digital finance and how this knowledge relates to their financial well-being. The subjects of the study were 100 leaders and owners of small industrial businesses in the Sukabumi City and Regency Areas. Data was collected using a questionnaire. The results concluded that SME owners that understand and implement finance literacy take significant steps toward improving their financial well-being. This implies that strengthening regulation and increasing the literacy index and could improve the financial well-being of the public. Keywords: Financial Welfare, Small and Medium Industries, Financial Literacy Digital